METAL-BEARING OF SOUTHERN ZANGEZUR NORAREVIK SUITE (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
Geological section of terrigenous coal-shale-continental sediments of southern Zangezur Norarevik suite is specified and substantiated the metal-bearing of the suite with promising gold-platinum mineralization.
Keywords: southern Zangezur; Norarevik suite; gold-platinum mineralization; terrigenous coal-shale-continental sediments